Societal Shifts in Central Asia: Figures and Trends - Yerkin Tukumov; Aidar Kurmashev (Journal of Central Asian Studies)
Central Asia has been undergoing considerable transformations by becoming mature independent states in international arena and experiencing socio-demographic shifts. It clearly resembles the dynamics described in Moises Naím’s “The end of power” where he argues that “the more, mobility, and mentality” revolutions challenge political leaders with fluid and unpredictable environment. This article aims to do an empirical analysis of the socio-demographic changes in Central Asia to test the assumption in the regional context.